Removal of organic pollutants, heavy metals and trace elements from sewage using Phragmites australis (Cav.) Trin. ex Steud. - Chandrasekaran , Sivaraman; Qari , Huda A (Bangladesh Journal of Botany, 2023)
Potential removal of emerging organic pollutants, heavy metals and trace elements using the reed plant Phragmites australis (Cav.) Trin. ex Steud was evaluated in the year 2020. HPLC analysis showed that the removal efficiency of pyrene and dibutyl phthalate at the end of four-week experiments were 87.37 ± 4.95% and 83.67 ± 5.62%, respectively. Investigation of heavy metals through ICP-AES showed that the efficiency of heavy metal removal was in order of Ba > Zn > As > Cu > Al > Pb > Cd > Cr > Ag. Trace elements such as P, K and Na were removed as high as 70 % from the sewage. Analysis of Phragmites sp., indicated that the removed heavy metals from sewage was mostly found in roots and less translocated to the shoot system. Hence this model study could be extrapolated so that P. australis could serve as efficient biomitigator for the removal of emerging organic pollutants, heavy metals, and trace elements. Bangladesh J. Bot. 52(1): 9-15, 2023 (March)